Pregabalin versus Montelukast in the management of uremic pruritus in hemodialysis patients - Aljader, Ruba; Mowafaq Ali, Samara (Iraqi Journal of Pharmaceutical Sciences, 2025)
Many patients with chronic kidney (CKD) disease experience uremic pruritus (UP), which lowers quality of life. The intensity of UP varies and can cause anything from occasional pain to total restlessness during the day or night. this trial aimed to compare the efficacy of pregabalin and montelukast in uremic pruritus among CKD undergoing hemodialysis. For four weeks, this was a randomize prospective- intervention trial. patients with end-stage renal disease, between the ages of 30 and 75, been on hemodialysis at least one year and persistently severe pruritus had been included. Patients were split into Group P (n=25) receiving 50 mg of pregabalin and Group M (n=25) receiving 10 mg of montelukast. Every week, the effectiveness of the medications was evaluated using a numeric rating scale (NRS) and a 5D itch score. Compared to baseline, montelukast and pregabalin reduce 5-D scale (p<0.05). Between the two medications, no noticeable distinctions were seen (p>0.05). the study concluded that montelukast and pregabalin medication, have a positive effect on reducing UP while there were no significant differences observed between the two drugs.